Research Advances of Purple Sweet Potato Anthocyanins: Extraction, Identification, Stability, Bioactivity, Application, and Biotransformation - Li, Aoran; Xiao, Ruoshi; He, Sijia; An, Xiaoyu; He, Yi; Wang, Chengtao; Yin, Sheng; Wang, Bin; Shi, Xuewei; He, Jingren (Molecules (Basel, Switzerland), 2019)
Purple sweet potato anthocyanins are kinds of natural anthocyanin red pigments extracted from the root or stem of purple sweet potato. They are stable and have the functions of anti-oxidation, anti-mutation, anti-tumor, liver protection, hypoglycemia, and anti-inflammation, which confer them a good application prospect. Nevertheless, there is not a comprehensive review of purple sweet potato anthocyanins so far. The extraction, structural characterization, stability, functional activity, application in the food, cosmetics, medicine, and other industries of anthocyanins from purple sweet potato, together with their biotransformation in vitro or by gut microorganism are reviewed in this paper, which provides a reference for further development and utilization of anthocyanins.